A Low Financial Literacy On The Desire To Do Online Loans (Case Study Of Muhammadiyah Surabaya University Students) - PUTRA, Bagas Laksana; RIFQI, Arfian Ambar; AL-MASYHURI, Samdan (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:The purpose of this study is to find out the Low Financial Literacy Against the Desire to Make Online Loans (Case Study of University of Muhammadiyah Surabaya Students).Methodology:The type of research used in this study is a qualitative method. In this qualitative method, the researcher conducts research by considering the situation and condition of the respondents. The data collection method used is by conducting interviews and documentation. Interviews were conducted with 90 management students at the University of Muhammadiyah Surabaya. Meanwhile, the following data collection method is the method of documentation or collecting information in journals.Findings:The results of the study showed that there were still many students who had a lack of understanding. Then, many students do not understand the impact caused by the dissemination of personal information data. Then, many students have not been able to calculate the risk that will be obtained if the payment exceeds the maturity date or even the risk of spreading illegal data.Implication:This study underscores the importance of equipping students with the necessary skills to navigate financial decisions responsibly. It can include educating them about the implications of sharing personal information, understanding the risks associated with late payments, and recognizing the dangers of spreading illegal data.